Design of two-quadrant zero voltage switching quasi resonant converter - Chelliah Thirugomathi. (2010)
This Project describes how soft-switching technique using Zero Voltage switching Quasi Resonant Converter (ZVS-QRC) provides power lossless switching transitions. Also it ensures reduced EMIIRFI at transitions, avoids high peak currents (which is present in the case of ZCS), better efficiency with high voltage at any frequency. Therefore, it largely reduces the power losses of the converter. Zero Voltage Switching can best be defined as conventional square wave power conversion during the switch's ON-time with "resonant" switching transitions. For the most part, it can be considered as square wave power utilizing a constant off-time control which varies the conversion frequency, or ON-time to maintain regulation of the output voltage. Regulation of the output voltage is accomplished by adjusting the effective duty cycle, performed by varying the conversion frequency, changing the effective ON-time in a ZVS design. In industries DC/DC converters are widely used. Since the classical converters and switched inductor converters have high power losses across the switches during switching-on and switching oft: the power transfer efficiency of these converters is limited. Most of the papers in literature introduce the Zero-Current-Switching (ZCS) and Zero-Voltage-Switching (ZVS) methods in single quadrant operation. This project introduces a two-quadrant DC/DC zero-voltage-switching (ZVS) quasi-resonant-converter, which effectively reduces the power losses, and largely increases the power density and power transfer efficiency. The two-quadrant DC/DC zero-voltage-switching (ZVS) quasi-resonant-converter is simulated by using Matlab/Simulink and it is tested for both soft and hard switching. The outcomes are compared and the results are found to be satisfactory.